Poloidal asymmetries in the edge density profiles on ASDEX Upgrade. (19th December 2017) - Guimarais, L.; Potzel, S.; Silva, C.; Bernert, M.; Carralero, D.; Conway, G.D.; Gil, L.; Manso, M.E.; Nikolaeva, V.; Reimold, F.; Santos, J.; Silva, A.; et al.
Abstract: The evolution of the midplane edge electron density profiles and its link to divertor detachment is studied on ASDEX Upgrade, taking advantage of the high resolution high-field-side (HFS) / low-field-side (LFS) O-mode reflectometry measurements. Ohmic and L-mode discharges were studied where detachment was achieved through density ramps. We have shown that the region of high density on the HFS (HFSHD) expands to the midplane, leading to strong poloidal asymmetries in the main chamber SOL density, which are quantified by defining an asymmetry parameter based on reflectometry data. The evolution of the midplane edge density profile in the HFS was observed to respond to divertor oscillations, changing significantly for different divertor detachment states. The HFS/LFS density asymmetry was found to increase with input power and to decrease with N 2 seeding.